2020
DOI: 10.1186/s12957-020-02113-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and laparoscopic liver surgery for colorectal liver metastases: an experience from a German Academic Center

Abstract: Background Minimally invasive liver surgery (MILS) in the treatment of colorectal liver metastases (CRLM) is increasing in incidence. The aim of this work was to present our experience by reporting short-term and long-term outcomes after MILS for CRLM with comparative analysis of laparoscopic (LLS) and robotic liver surgery (RLS). Methods Twenty-five patients with CRLM, who underwent MILS between May 2012 and March 2020, were selected from our retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 17 publications
(39 reference statements)
3
32
1
Order By: Relevance
“…Clavien-Dindo complications of grade 3 and above occurred in 4-6% of the laparoscopic patients, 0-22% in the robotic cohort and 25-35% in the open cohort and, although this difference was statistically significant only when the LLR was compared to the OLR group, these rates are well within the range published in the literature of 5-55% after laparoscopic hepatectomy, 17-20% after robotic resection and 17-61% after open hepatectomy [33,35,36]. The major cause of morbidity after major liver resection is bile leak with 13.5% of patients after major hepatectomy found to have a bile leak in one study [37].…”
Section: Discussionsupporting
confidence: 72%
“…Clavien-Dindo complications of grade 3 and above occurred in 4-6% of the laparoscopic patients, 0-22% in the robotic cohort and 25-35% in the open cohort and, although this difference was statistically significant only when the LLR was compared to the OLR group, these rates are well within the range published in the literature of 5-55% after laparoscopic hepatectomy, 17-20% after robotic resection and 17-61% after open hepatectomy [33,35,36]. The major cause of morbidity after major liver resection is bile leak with 13.5% of patients after major hepatectomy found to have a bile leak in one study [37].…”
Section: Discussionsupporting
confidence: 72%
“…When we compared cases done with HR vs. CR, similar to other studies, we found that cases done with the CR approach were statistically longer than after HR [Table 3], but estimated blood loss was not higher as in most studies [35] . It is unclear if more complex liver resections will one day be done by the CR approach as suggested by this German study [36] , but what is clear is that whatever approach a surgeon is most comfortable with is clearly better for outcomes in the short term [37] .…”
Section: Discussionsupporting
confidence: 80%
“…Comparing our data with data reported by referral centres for HPB surgery with a huge experience in laparoscopic liver surgery, so we can underline that through the robot assisted approach, general surgeons even if they are not dedicated to HPB may achieve perioperative outcomes superimposable to the standard of care. 25,27,28,30 4.9 | Costs None of the included studies reported cost data. One of the most popular drawbacks of robotic surgery is its cost-effectiveness, which is apparently more disadvantageous than conventional techniques.…”
Section: Volume and Centresmentioning
confidence: 99%